2002
DOI: 10.1038/sj.ejcn.1601509
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fats and 16-year coronary heart disease mortality in a cohort of men and women in Great Britain

Abstract: Objective: The paper aims to investigate the relationships of dietary fats to subsequent coronary heart disease (CHD) mortality in men and women while taking account of other CHD-related behaviours. Design: A cohort of randomly selected men and women were interviewed in 1984 -85 and monitored subsequently for 16 y for deaths. The interview covered health, health-related behaviours, physical measurements, socio-demographic details and a dietary questionnaire. Appropriate exclusions left 1225 men and 1451 women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 42 publications
4
45
1
4
Order By: Relevance
“…Fish was found to be protective against death from CHD (He et al, 2004;Zhang et al, 2009), high intakes of saturated fats were found to increase the risk in women, but not in men (Boniface and Tefft, 2002), and oils rich in a-linolenic acid were identified to lower CHD mortality (Zatonski et al, 2008), but results have not always been consistent.…”
Section: Discussionmentioning
confidence: 97%
“…Fish was found to be protective against death from CHD (He et al, 2004;Zhang et al, 2009), high intakes of saturated fats were found to increase the risk in women, but not in men (Boniface and Tefft, 2002), and oils rich in a-linolenic acid were identified to lower CHD mortality (Zatonski et al, 2008), but results have not always been consistent.…”
Section: Discussionmentioning
confidence: 97%
“…Os resultados de pesquisas epidemiológicas corroboraram com a hipótese de que o tipo de gordura é um determinante mais importante do risco cardiovascular que a sua quantidade total. Ensaios clínicos também mostraram que a substituição de ácido graxo saturado e gorduras trans da dieta por ácido graxo polinsaturado é mais efetiva na redução dos níveis séricos de colesterol e da morbi-mortalidade por doenças cardiovasculares que a simples redução do teor total de lípides da dieta (65,(67)(68)(69)(70)(71)(72)(73)(74)(75). A recomendação atual é a de estimular o consumo de óleos vegetais (especialmente os de oliva e canola), de peixes e frutas oleaginosas, e reduzir o de alimentos ricos em gorduras saturadas e trans.…”
Section: Discussionunclassified
“…Nonetheless, the association between SFA intake and IHD has been controversial. SFA intake has been shown to be positively associated with the risk of IHD (4,5), and replacing SFA intake with polyunsaturated fatty acid (PUFA) intake was associated with a lower risk of IHD (6). SFA intake, however, was inversely associated with the progression of coronary atherosclerosis (7).…”
Section: Introductionmentioning
confidence: 95%